The Construction of Complex Sentences with Predicative Phrases of Transitive Verbs in Japanese Language Learners Utterances: A Transformational Generative Grammar Study - Mintarsih Mintarsih (JAPANEDU: Jurnal Pendidikan dan Pengajaran Bahasa Jepang, 2023)
This research examines how fukubun (complex sentence) with transitive verbs is constructed in the utterance of Japanese language learners in universities. The fukubun constructions are described and analyzed through transformational generative grammar. This research method is descriptive-qualitative, with data collection techniques in the form of semi-structured interviews. Data analysis uses an analytical approach of transformational generative grammar, namely analysis of phrase structure rules and analysis of the transformation process. The results showed that there were 4 (four) types of B-derived constructs, namely: BB type, BB (1) type, BB (2) type, and BB (3) type. Among the four types of derivatives, type BB construction is dominant in the utterance of learners. This is indicated by the tendency to use the BB-type construction when describing various situations, even though the utterance events use various conjunctions. The dominance of the BB-type shows that the utterances by learners are still relatively simple because it only requires one object in the subordination clause and main clause. Furthermore, B fukubun found eight varieties of conjunctive transformation used in this type. All varieties of conjunctive transformation appeared in the BB-type construction, with relatively frequent use of causality, serial, selection/alternative, and temporal conjunctions. The T-process analysis shows several tendencies in the elementary transformation process in the utterance, namely the omission of the subject in both the subordination clause or the main clause, the merger of the subject or the predicate of the verb, whereas in causality conjunctive transformation learners showed a more varied and complex T-process.